Antibacterial and Antibiofilm Effects of Green Tea and Salvadora Persica L. Extracts Against Clinically Isolated Porphyromonas gingivalis: An in Vitro Study - Abdulkareem, Murtadha Imad; Abdulbaqi, Hayder Raad; Sha, Aram Mohammed; Al-Taweel, Firas Bashir Hashim; Shaikh, Muhammad Saad Shaikh (Kurdistan Journal of Applied Research, 2023)
The combination of an aqueous extract of green tea (GT) and Salvadora persica L. (SP) was proved to prevent the growth of Gram +ve facultative anaerobes and reduce biofilm formation on teeth surfaces. Porphyromonas gingivalis (P. gingivalis) is amongst the red complex pathogenic bacteria that cause periodontal disease. Thus, the aim of the current study was to examine the antibacterial and antibiofilm effects of the above combination in reducing the growth of P. gingivalis. Subgingival dental biofilm samples were collected from patients with severe periodontitis to isolate and confirm the presence of P. gingivalis. Gas mass chromatography-mass spectrometry was used for phytochemical analysis. The maceration method was used to extract the GT and SP. Disc diffusion and broth dilution methods were performed to determine antibacterial and minimum inhibitory concentrations (MIC) of SP, GT aqueous extract, and their combination in contrast to clinically isolated P. gingivalis. Further, the antibiofilm activity of the extracts and their combination was assessed using the tube adhesion technique. The findings showed that only the GT aqueous extract was effective against P. gingivalis, while the SP aqueous extract demonstrated no effectiveness. The MIC of GT was 6.25mg/mL. The aqueous extract of SP showed a greater antibiofilm effect than the aqueous extract of GT at the lowest concentrations of 6.25mg/mL and 12.5mg/mL, respectively. In conclusion, the antibacterial property of the SP and GT extracts combination against P. gingivalis was attributed to GT only. While SP extract displayed no inhibitory role against P. gingivalis, it could potentially reduce the biofilm attachment of P. gingivalis better than GT extracts.